Multiple Gamma-Ray Detection Capability of a CeBr3 Detector for Gamma Spectroscopy - Naqvi, A. A.; Khiari, F. Z.; Liadi, F. A.; ur-Rehman, Khateeb; Raashid, M.; Isab, A. A. (Journal of Spectroscopy, 2017)
The newly developed cerium tribromide (CeBr3) detector has reduced intrinsic gamma-ray activity with gamma energy restricted to 1400–2200 keV energy range. This narrower region of background gamma rays allows the CeBr3 detector to detect more than one gamma ray to analyze the gamma-ray spectrum. Use of multiple gamma-ray intensities in elemental analysis instead of a single one improves the accuracy of the estimated results. Multigamma-ray detection capability of a cylindrical 75 mm × 75 mm (diameter × height) CeBr3 detector has been tested by analyzing the chlorine concentration in water samples using eight chlorine prompt gamma rays over 517 to 8578 keV energies utilizing a D-D portable neutron generator-based PGNAA setup and measuring the corresponding minimum detection limit (MDC) of chlorine. The measured MDC of chlorine for gamma rays with 517–8578 keV energies varies from 0.07 ± 0.02 wt% to 0.80 ± 0.24. The best value of MDC was measured to be 0.07 ± 0.02 wt% for 788 keV gamma rays. The experimental results are in good agreement with Monte Carlo calculations. The study has shown excellent detection capabilities of the CeBr3 detector for eight prompt gamma rays over 517–8578 keV energy range without significant background interference.